N2: On integrated rainwater management strategies – technologies, institutions and policies - Bossio, Deborah A.; Awulachew, Seleshi Bekele; McCartney, Matthew P.; Rebelo, Lisa-Maria; Mapedza, Everisto D. (2010)
Integrated rainwater management strategies combine technologies, policies and institutions. Work in this project will aim to integrate land and water management, crop component technology, crop management, crop livestock systems, pastoral systems and even agroforestry systems so as to raise productivity and incomes and enhance resilience, while slowing land degradation and reducing downstream siltation. It is clear, however, that the shape of policies and institutions can foster or discourage farmer adoption of productivity-increasing, resource-conserving strategies. This project will also examine the extent to which policy change and institutional strengthening and reform can combine with new technologies to spur widespread innovation. It will look into micro-credit, cooperative societies, land tenure, collective action in communities, and the various roles of formal and informal institutions, as part of integrated strategies to improve rainwater management.